Association between early pregnant hospitalization and use of obstetric interventions and cesarean: a cross-sectional study - Tamara Lopes Terto; Thales Philipe Rodrigues da Silva; Thamara Gabriela Fernandes Viana; Ana Maria Magalhães Sousa; Eunice Francisca Martins; Kleyde Ventura de Souza; Fernanda Penido Matozinhos
ABSTRACT Objective: Evaluate the association between early pregnant hospitalization and the use of obstetric interventions and cesarean delivery route. Methods: Cross-sectional study, with 758 women selected at the time of childbirth. It was assumed as early hospitalization when the woman was admitted to the hospital having less than 6 cm of cervical dilation. Logistic regression models were constructed in order to estimate the odds ratio for each obstetric intervention, adjusted by sociodemographic and obstetric variables. Results: 73.22% of women were early hospitalized. On average, they had 1.97 times the chance to undergo Kristeller's maneuver, 2.59 and 1.80 times the chance to receive oxytocin infusion and analgesia, respectively, and 8 times more chances to having their children by cesarean delivery when compared to women that had timely hospitalization. Conclusion: Early hospitalized women were submitted to a higher number of obstetric intervention and had increased chances of undergoing cesarean sections.